2018
DOI: 10.1177/0272989x18786358
|View full text |Cite
|
Sign up to set email alerts
|

Double Conjunction Fallacies in Physicians’ Probability Judgment

Abstract: We report the first empirical data showing a significant amount of double conjunction fallacies in physicians' probability judgments concerning prognosis and diagnosis. Our results support the hypothesis that physicians' probability judgments are guided by assessments of evidential impact between diagnostic conditions and clinical signs. Moreover, we show that, contrary to some influential views, double conjunction fallacies represent an experimentally replicable reasoning bias. We discuss how the phenomenon e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
3
2
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 13 publications
(17 citation statements)
references
References 16 publications
2
15
0
Order By: Relevance
“…Similar results have been documented not only with a variety of hypothetical scenarios, but also in many real-life domains, both for laypeople and experts who had been asked for probability judgments in their own fields of specialization (e.g., Frederick and Libby (1986), Ho and Keller (1994), Tversky and Kahneman (1983), Adam and Reyna (2005), Garb (2006), Crupi et al (2018)).…”
Section: The Conjunction Fallacysupporting
confidence: 78%
See 1 more Smart Citation
“…Similar results have been documented not only with a variety of hypothetical scenarios, but also in many real-life domains, both for laypeople and experts who had been asked for probability judgments in their own fields of specialization (e.g., Frederick and Libby (1986), Ho and Keller (1994), Tversky and Kahneman (1983), Adam and Reyna (2005), Garb (2006), Crupi et al (2018)).…”
Section: The Conjunction Fallacysupporting
confidence: 78%
“…To appreciate the relationship between confirmation and explanation, it might be of help to refer to the following CF scenario, which has been recently presented to 82 experienced internists (Crupi et al, 2018).…”
Section: What Suggestions For Effective Human-like Computing?mentioning
confidence: 99%
“…Similar results have been documented not only with a variety of hypothetical scenarios, but also in many real-life domains, both for laypeople and experts who had been asked for probability judgments in their own fields of specialization (e.g., Frederick and Libby (1986), Ho and Keller (1994), Tversky and Kahneman (1983), Adam and Reyna (2005), Garb (2006), Crupi et al (2018)).…”
Section: The Conjunction Fallacysupporting
confidence: 78%
“…We found one article where it is shown that half of early medical students estimated the probability that a patient with a common cold would experience the symptoms of 'runny nose and diarrhea' to be higher than that of the patient experiencing the symptom of 'diarrhea' [33]. However, we also found a very recent and thorough investigation where an impressive amount of data was obtained, showing the occurrence of the double conjunction fallacy in a systematic way in medicine [34]. The data collected in this work interests us particularly, because, as the authors themselves recognize, there are actually no convincing models of decision-making for the double conjunction fallacy [35,36,37,38,39].…”
mentioning
confidence: 65%
“…The authors of the above-mentioned study disagree with this view and claim that their experiments show that double conjunction fallacies are no exception and appear abundantly whenever some specific cognitive situations arise. What is interesting is that in the quantum model of the pet-fish situation that we developed in our group [17,26,27,28,29], the single and double conjunction fallacies can be modeled in a very natural way, and result both from a same fundamental mechanism, which we plan to use also as an explanation for, and to further the analysis of, the situations put forward in [34].…”
mentioning
confidence: 99%